OPTIMALISASI PERAN MASYARAKAT SAWAI DALAM PEMANFAATAN TANAMAN LOKAL TERHADAP KERAWANAN PANGAN DI KECAMATAN WEDA TENGAH - usman amiruddin; Faisal Y Habsyi; Bakrin Abu (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study discusses the optimization of the role of the Sawai community in utilizing local plants to overcome food insecurity in Weda Tengah District. The community has great potential in planting, caring for, and developing plants such as sago, sweet potatoes, taro, and bananas which are part of the traditional food system. Local knowledge that is passed down from generation to generation can be utilized to create sustainable food security while opening up new business opportunities. However, the role of the community has not been optimal due to various obstacles such as degradation of agricultural land due to mining activities, dependence on food from outside the region, and weak institutional and policy support. In addition, access to training, technology, and markets is still limited, and there has been a decline in the regeneration of local knowledge. However, local plants still have great potential as a solution to food insecurity if they receive targeted and sustainable support. Therefore, community empowerment based on local wisdom needs to be improved in the regional food security development strategy